Millennial-scale variations in dustiness recorded in Mid-Atlantic sediments from 0 to 70 ka - Middleton, Jennifer L.; Mukhopadhyay, Sujoy; Langmuir, Charles H.; McManus, Jerry F.; Huybers, Peter J. (Earth and Planetary Science Letters, 2018)
Sedimentary records of dust deposition in the subtropical Atlantic provide important constraints on millennial- and orbital-scale variability in atmospheric circulation and North African aridity. Constant flux proxies, such as extraterrestrial helium-3, yield dust flux records that are independent of the biases caused by lateral sediment transport and limited resolution that may be associated with age-model-derived mass accumulation rates. However, Atlantic dust records constrained using constant flux proxies are sparsely distributed and generally limited to the past 20 ka. Here we extend the Atlantic record of North African dust deposition to 70 ka using extraterrestrial helium-3 and measurements of titanium, thorium, and terrigenous helium-4 in two sediment cores collected at 26°N and 29°N on the Mid-Atlantic Ridge and compare results to model estimates for dust deposition in the subtropical North Atlantic. Dust proxy fluxes between 26°N and 29°N are well correlated, despite variability in lateral sediment transport, and underscore the utility of extraterrestrial helium-3 for constraining millennial-scale variability in dust deposition. Similarities between Mid-Atlantic dust flux trends and those observed along the Northwest African margin corroborate previous interpretations of dust flux variability over the past 20 ka and suggest that long distance transport and depositional processes do not overly obscure the signal of North African dust emissions. The 70 ka Mid-Atlantic record reveals a slight increase in North African dustiness from Marine Isotope Stage 4 through the Last Glacial Maximum and a dramatic decrease in dustiness associated with the African Humid Period. On the millennial-scale, the new records exhibit brief dust maxima coincident with North Atlantic cold periods such as the Younger Dryas, and multiple Heinrich Stadials. The correlation between Mid-Atlantic dust fluxes and previous constraints on North African aridity is high. However, precipitation exerts less control on dust flux variability prior to the African Humid Period, when wind variability governs dust emissions from consistently dry dust source regions. Thus, the Mid-Atlantic dust record supports the hypothesis that both aridity and wind strength drive dust flux variability across changing climatic conditions.
Keywords: helium-3; mass accumulation rate; mineral dust; North Africa; Subtropical North Atlantic; thorium-232